Relationship Of Chronic Energy Deficiency During Pregnancy With Stunting In Toddlers Aged 6-60 Months - Iramaya Sari; Marwidah; Mitra Asriani Amin; Nihlawani Dg.Pasau (Jurnal Life Birth, 2022)
Stunting is a form of growth failure (growth faltering) due to the accumulation of nutritional deficiencies that last a long time starting from the time of pregnancy. The purpose of the study is to find out the relationship between the incidence of chronic energy deficiency (SEZ) during pregnancy and the incidence of stunting in toddlers 6-60 months. This type of research is a case-control study with a retrospective observational approach. The study subjects were children aged 6-60 months as many as 86 respondents in the case group were stunting children (43 people) and the control group was a normal child (43 people) based on PB / U indicators matching the residence of the case group and control Data sampling techniques with simple random sampling, univariate analyzed, bivariate (chi-square test) and multivariate (double logistic regression). The results of this study are: there is a meaningful relationship between SEZ in pregnant women (p = 0.001, ), BBLR (p = 0.044) and not exclusive breastfeeding (p = 0.018) with exclusive stunting events (p = 0.018), with exclusive stunting events (p = 0.018), with exclusive stunting events (p = 0.044) and non-exclusive stunting events (p = 0.044 ) and non-exclusive breastfeeding (p = 0.044) and non-exclusive stunting events (p = 0.044) and non-exclusive breastfeeding (p = 0.018) and exclusive breastfeeding (p = 0. 026). Low maternal education, authoritarian/permissive parenting, anemia during pregnancy, high-risk maternal age, and short maternal stature have no meaningful relationship with stunting. SEZ is the dominant factor that affects stunting. The chance of a toddler becoming stunted if the mother of SEZ, the baby is born with BBLR and not exclusively breastfed by 98%. The conclusion is that there is a meaningful relationship between the incidence of SEZ during pregnancy and stunting in toddlers (6-60 months).